Correlation Between Plasma CircRNA-089763 and Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Non-cardiac Surgery - Zhou, Hongli; Li, Fuyu; Ye, Wanlin; Wang, Maozhou; Zhou, Xian; Feng, Jianguo; Liu, Li; Wang, Xiaobin (Frontiers in Behavioral Neuroscience, 2020)
In our previous experiment, we found that there were abnormal levels of circRNA-089763 in the plasma exosomes of patients with postoperative cognitive dysfunction (POCD) after cardiac surgery. Therefore, the aim of this study was to further investigate the relationship between plasma circRNA-089763 level and POCD in elderly patients after non-cardiac surgery. A prospective cohort study was conducted to select elderly patients undergoing elective non-cardiac surgery. A total of 72 patients were enrolled in this study, and cognitive functions were assessed 1 day before and 3 days after surgery by a series of neuropsychological measurements. Next, patients were divided into POCD and non-POCD (NPOCD) groups according to the Z score method. Blood was collected the day before and 3 days after surgery, and the plasma circRNA-089763 level was detected by quantitative real-time polymerase chain reaction (qRT-PCR). Then, the difference and correlation in plasma circRNA-089763 levels between the POCD and NPOCD groups were analyzed. On the third day after surgery, the incidence of POCD was 30.56%. The relative level of circRNA-089763 in the POCD group was 2.41 times higher than that in the NPOCD group (t = 4.711, p < 0.001), patients in POCD group had higher age (t = 5.971, p < 0.001), higher American Society of Anesthesiologists classification (χ2 = 14.726, p < 0.001), less years of education (t = 2.449, p = 0.017), more intraoperative blood loss (t = 3.196, p = 0.002), and higher visual analog scale (VAS) scores (t = 10.45, p < 0.001). The binary logistic regression analysis showed that the circRNA-089763 level, age, and intraoperative blood loss were independently associated with POCD (OR: 2.75, 95% CI: 1.261–5.999, p = 0.011; OR: 1.32, 95% CI: 1.114–1.565, p = 0.001; OR: 1.017, 95% CI: 1.004–1.03, p = 0.011). These results demonstrated that the circRNA-089763 plasma level was related to POCD after non-cardiac surgery in elderly patients.